Prevalence and determinants of abnormal glucose metabolism in urban and rural secondary schools in Cameroon: A cross-sectional study in a sub-Saharan Africa setting. Issue 4 (August 2019) - Kamdem, Félicité; Lemogoum, Daniel; Jingi, Ahmadou Musa; Guetchuin, Stéphane Choupo; Kenmegne, Caroline; Solange Doualla, Marie; Luma, Henry
Highlights: There is paucity of data on the Burden of abnormal glucose metabolism in secondary schools. This study showed a high rate of abnormal glucose metabolism in secondary schools. The burden was higher in rural schools. This was fueled by high rates of abdominal obesity. Abstract: Introduction: The incidence of Diabetes in children and teenagers increased by 30.2% between 2001 and 2009, with the main cause being an increase in the prevalence of overweight and obesity. Despite its high morbidity and mortality, few studies in Cameroon have focused on the study of abnormal glucose metabolism in schools. Methodology: This cross-sectional study was carried out in three schools institutions of two health districts selected from a three-stage cluster sampling survey–which consisted of a simple draw without discount for department selection, a simple random survey for the choice of health districts, and finally a simple random survey for the choice of schools institutions. Results: Among the 815 participants, the prevalence of impaired fasting glucose and diabetes was 34.1% and 1.8% respectively. Glucose metabolism abnormalities were significantly higher in rural area than in urban areas (40% vs. 31.6%, p = 0.016), and were significantly associated with abdominal obesity (p = 0.027). Overweight and obesity were significantly higher in rural areas (p = 0.0002), as well as abdominal obesity (p = 0.0004). Conclusion: Abnormalities of glucose metabolism are a major health problem in schools in Cameroon. Thus, it is urgent to develop a health policy involving teachers and parents in the fight against overweight and obesity in schools.